MicroRNAs as Promising Therapeutic Agents Against Prostate Cancer Resistant to Castration-Where Are We Now? - Mariana Ferreira; Mariana Morais; Rui Medeiros; Ana Luísa Teixeira (MDPI AG, 2024)
MicroRNAs are a conserved class of small, tissue-specific, non-coding RNAs that regulate gene expression to preserve cellular homeostasis. Proper miRNA expression is crucial for physiological balance because it affects numerous genetic pathways, including cell cycle control, proliferation, and apoptosis, through gene expression targeting. Deregulated miRNA expression has been implicated in several cancer types, including prostate cancer (PC), acting as tumor suppressors or oncogenes. Despite the availability of promising therapies to control tumor growth and progression, effective diagnostic and therapeutic strategies for different types of cancer are still lacking. PC continues to be a significant health challenge, particularly its castration-resistant (CRPC) form, which presents major therapeutic obstacles because of its resistance to conventional androgen deprivation treatments. This review explores miRNAs' critical roles in gene regulation and cancer biology, as well as various miRNA delivery systems, highlighting their potential and the challenges in effectively targeting cancer cells. It aims to provide a comprehensive overview of the status of miRNA research in the fight against CRPC, summarizing miRNA-based therapies' successes and limitations. It also highlights the promise of miRNAs as therapeutic agents for CRPC, underlining the need for further research to overcome existing challenges and move these therapies toward clinical applications.